PERANCANGAN APLIKASI PENJADWALAN TURNAMEN FUTSAL BERBASIS WEB - Aditya Iswandi; Dinda Ayu Muthia; Hanafi Eko Darono (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2022)
Currently, futsal has developed in various cities and regions. Futsal is a soccer game that is usually played indoors with a smaller field size than a football field. In a futsal tournament held in a certain area, the implementation of the tournament system is still done manually. The author designed a web-based futsal tournament scheduling application using the waterfall method. The web created can make it easier for admins to manage tournament data, teams, groups, tournament schedules and results, along with standings. In addition, this website can also produce fast and accurate information about the tournament to be held.